2017
DOI: 10.1111/eci.12752
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase and prognosis in patients with coronary artery disease

Abstract: Background The evidence on the association between alkaline phosphatase (ALP) and prognosis of patients with coronary artery disease (CAD) is limited. The aim of this study was to assess the association of ALP with the risk of mortality or coronary events in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
(54 reference statements)
0
28
0
Order By: Relevance
“…Another question is whether the local or systemic TNAP activity drives vascular calcification. Epidemiological studies clearly show that increased blood alkaline phosphatase activity correlates with coronary artery calcification [15, 16]. Therefore, it is plausible that circulating enzyme can be deposited into vascular tissues to increase calcification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another question is whether the local or systemic TNAP activity drives vascular calcification. Epidemiological studies clearly show that increased blood alkaline phosphatase activity correlates with coronary artery calcification [15, 16]. Therefore, it is plausible that circulating enzyme can be deposited into vascular tissues to increase calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Increased TNAP expression has also been detected in patients suffering from vascular calcification associated with diabetes [12] and chronic kidney disease [13, 14]. Recent epidemiological studies point to a potential pathophysiological role and a prognostic value of increased blood alkaline phosphatase activity in human coronary artery disease [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…They found that ALP was an independent predictor of adverse outcomes among 4115 participants with a previous myocardial infarction 11. This observation then was verified and extended by other researches that elevated ALP was an independent predictor of adverse outcomes in patients with CAD,12 13 ACS14 15 and STEMI 16 17. However, no study focuses on the prognostic value of ALP for in-hospital mortality in patients with ACS undergoing PCI.…”
Section: Discussionmentioning
confidence: 85%
“…Opposite to PTH, an association of serum osteocalcin with cardiovascular death is unclear, being U-shaped as well as gender-and age-dependent [31][32][33]. Data regarding the prognostic significance of alkaline phosphatase are also contradictory, varying between revascularisation modalities [34][35][36]. Albeit serum alkaline phosphatase may be also increased in patients with stroke, chronic heart failure, arterial hypertension, type 2 diabetes mellitus, and obesity, a number of studies showed its usefulness as a prognostic indicator during the long-term follow-up of patients with coronary artery disease [35,36] including those with ST-segment elevation MI [37].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the prognostic significance of alkaline phosphatase are also contradictory, varying between revascularisation modalities [34][35][36]. Albeit serum alkaline phosphatase may be also increased in patients with stroke, chronic heart failure, arterial hypertension, type 2 diabetes mellitus, and obesity, a number of studies showed its usefulness as a prognostic indicator during the long-term follow-up of patients with coronary artery disease [35,36] including those with ST-segment elevation MI [37]. In addition, SAP of CCS grade IV, New York Heart Association class IV chronic heart failure, and obesity were among the criteria of exclusion in our study.…”
Section: Discussionmentioning
confidence: 99%